Factors influencing Islamic credit card usage among employees of Naza Eftra Trading, Petaling Jaya / Hazimah Soleha Ismail - Ismail, Hazimah Soleha (Faculty of Business and Management, 2015)
The purpose of this study was examine the factors influencing Islamic credit cards usage among employees in NAZA Eftra Trading, Petaling Jaya. Here, researchers are going to look into on objective of the study whether the factors influencing of financial attitudes, financial knowledge and family influence that give influence towards Islamic credit card usage. This study carried out to get respondents feedback on NAZA Eftra Trading, Petaling Jaya. There were 100 respondents randomly chosen from all departments as well. In order to fulfil the objectives of the study, questionnaires form have been distributed to respondents to get the research information. The data collections were analysed by Statistical Package for Social Science (SPSS). The finding results showed the factors influencing of Islamic credit card usage is financial attitude because from the attitude respondent most preferable by using Islamic credit card. From this study the researchers hope that, terms and condition by applying Islamic credit card must be more details and particular. It is because the numbers of bankruptcy every year are keep rising especially for Malay. Lack of awareness and knowledge make them burden with credit card debt just because want to live with comfortable lifestyle without concerned if they pretend to fail pay credit card debt.